2023
DOI: 10.3390/educsci13111119
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Motivation When Using Multiple-Try in a Digital Game for Primary Students in Chile

Claudio Cubillos,
Silvana Roncagliolo,
Daniel Cabrera-Paniagua

Abstract: The number of attempts to provide students is a key instructional characteristic in computer-based learning (CBL). However, it has not been covered extensively, and there is a need to delve deeper into the factors affecting multiple-try performance and allowing its successful use, including the learner’s involved emotional processes. This study examines the effects of multiple-try on a drill-and-practice mathematical game devoted to primary school students. A total of 73 students from four courses from two sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…Furthermore, the present results show no learning differences among the two instructional conditions involved in this experiment, namely STF and MTF. Such contradicts past research supporting the idea of MTF outperforming STF in high-order or complex learning outcomes that are not just verbatim tasks [39,50,63,74].…”
Section: Rq1: Is There a Difference In Learning Outcomes Between Male...mentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, the present results show no learning differences among the two instructional conditions involved in this experiment, namely STF and MTF. Such contradicts past research supporting the idea of MTF outperforming STF in high-order or complex learning outcomes that are not just verbatim tasks [39,50,63,74].…”
Section: Rq1: Is There a Difference In Learning Outcomes Between Male...mentioning
confidence: 59%
“…In our previous study utilizing MatematicaST [74], the focus was on contrasting multiple-try feedback and a single-try condition with KCR among primary school students. The results revealed that MTF provided higher learning while exhibiting higher levels of perceived competence and autonomy than single try with KCR.…”
Section: Motivation and Self-determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…“MatematicaST” is a web platform with mathematical games, developed by our research group starting in 2017 as part of a Research & Development project. It has been piloted in elementary school courses in Chile, ranging from the 3rd to the 6th grade (from 8 to 11 years old), across various schools to practice mathematical topics [ 68 ]. For the current intervention, three math mini-games were offered: number identification, number ordering, and money counting (see Figure 1 ), aligned with the national curriculum for the 3rd and 4th grades in Chile.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study utilizing MatematicaST [ 68 ], the focus was on contrasting multiple-try feedback and the single-try condition with KCR among primary-school students. The results revealed that MTF provided higher learning and higher levels of perceived competence and autonomy than the single-try condition with KCR.…”
Section: Introductionmentioning
confidence: 99%